Proceedings of the Workshop on Global Market Integration and the Agri-Food Sector - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
112 páginas pdf.